The analysis of President Jokowi's Speech at the 2014 APEC CEO Summit in China - Masrul Huda (Musamus Journal of Language and Literature, 2021)
The speech was chosen because it was the first time President Jokowi used English in a speech at an international forum. This speech became a hot topic among economists because at that time Indonesia was experiencing an unstable economic situation. The research purposes are to describe the types and functions of speech acts and to describe the obedience and deviation of the politeness principles in President Jokowi's speech. The method used in this research is descriptive method, describing data based on existing facts or phenomena that are empirically alive to its speakers, resulting in notes in the form of language descriptions. The conclusions are (1) There are various types of illocutionary speech acts: assertive speech acts, commissive speech acts, expressive speech acts, expressive speech acts, and declarative speech acts. (2) Realization of obedience and deviation of President Jokowi's speech, including two utterances adhere to the maxims of wisdom, one utterance adheres to the maxim of humility, one deviation from the maxim of generosity, and two utterances deviate from the maxim of humility. (3) There are no utterances containing obedience or deviation from the maxims of praise, agreement, and maxim of sympathy.